Interval Kalman filter enhanced by positive definite upper bounds - Tran, Tuan Anh; Jauberthie, Carine; Gall, Françoise Le; Travé-Massuyès, Louise (IFAC-PapersOnLine, 2017)
A method based on the interval Kalman filter for discrete uncertain linear systems is presented. The system under consideration is subject to bounded parameter uncertainties not only in the state and observation matrices, but also in the covariance matrices of Gaussian noises. The gain matrix provided by the filter is optimized to give a minimal upper bound on the state estimation error covariance for all admissible uncertainties. The state estimation is then determined by using interval analysis in order to enclose the set of all possible solutions with respect to the classical Kalman filtering structure.